The impact of basketball on the physical health of Chinese middle school students aged 12–18: a systematic review and meta-analysis - Richen, Sun; Xiaolong, Xu; Weilong, Lin; Xiaoning, Sun; Hengtong, Wang (Frontiers in Public Health, 2025)
PurposeThis systematic review evaluates the impact of basketball on the physical fitness of Chinese middle school students, providing evidence-based support for research on how basketball enhances the physical health of Chinese students aged 12–18.MethodUsing CNKI, WanFang, WeiPu, PubMed, Web of Science, Embase, and Cochrane as search databases, the search period spanned from the inception of each database to March 4, 2025. Literature screening was conducted using the PICOST model. Ultimately, nine publications comprising 16 studies were included. Quality assessment was conducted using the PRISMA statement and the Cochrane Handbook for Systematic Reviews of Interventions. Statistical analysis and publication bias testing were performed using Review Manager 5.4 and Stata 17 software.ResultThe study included 736 secondary school students, comprising 387 in the experimental group and 349 in the control group. Meta-analysis findings indicate that basketball positively impacts secondary school pupils' physical fitness, with statistically significant outcomes. However, effects vary across different fitness components. Basketball demonstrated statistically significant effects on 50 m sprint performance [MD = −0.41 s, 95% CI (−0.45, −0.36), P < 0.00001]. Basketball training also produced statistically significant effects on sit-and-reach flexibility [MD = 2.22 cm, 95% CI (1.02, 3.41), P = 0.0003 < 0.05]. Basketball participation yielded statistically significant effects on middle school students' standing long jump performance [MD = 4.18 cm, 95% CI (2.56, 5.79), P < 0.00001]. Basketball participation had statistically significant effects on middle school students' sit-up performance [MD = 4.58 t, 95% CI (2.66, 6.50), P < 0.00001]. Basketball participation had a statistically significant effect on secondary school students' 1,000 m performance [MD = −11.70 s, 95% CI (−20.00, −3.39), P = 0.006 < 0.05]. Basketball participation had a statistically significant effect on secondary school pupils' 800 m performance [MD = −10.59 s, 95% CI (−15.46, −5.72), P < 0.0001]. However, basketball participation did not yield statistically significant effects on pull-up performance.ConclusionBasketball training yields comprehensive benefits for enhancing the physical fitness of secondary school students, with improvements primarily observed in speed, flexibility, strength, and endurance. However, no significant enhancement in upper-body strength was noted. The extent of improvement varied according to gender, year group, and duration of the intervention programme.Systematic review registrationPROSPERO, identifier CRD420251022157.